Research of the Process of Separation of Carbon Waste in the Central Energy Region - Zhumaev, K. K.; Makhmudova, N. S.; Shomurodov, A. Yu. (European Journal of Life Safety and Stability (2660-9630), 2021)
The aim of our research is to develop a comprehensive technology for the disposal of oil sludge, from researching the characteristics of oil sludge and the physico-chemical basis of the process to issuing practical recommendations for a feasibility study for the construction of a pilot plant for the utilization of oil sludge. Studies have been conducted to determine the influence of various factors on the separation of oil sludge in the field of centrifugal forces. Experimental work was carried out in laboratory conditions to determine the effectiveness of various schemes for including hydrocyclones.